Profile of the cases of violence reported in university hospital - Silva, Aline do Nascimento; Gomes, Eduardo Tavares; Melo, Renata Livia Alves de Souza; Siqueira, Rutheanne Melo de; Fonteles, Lucileide Silva (Revista de Enfermagem UFPE on line, 2010)
ABSTRACT Objective: to elucidate the situation of the notification of cases of violence in a university in a university hospital in Recife at the beginning of training actions and professional awareness of this issue. Method: an observational cross-sectional study as conducted. Data collection was done through referrals made to the Social Service of Clinics Hospital of the Federal University of Pernambuco (HC/UFPE), by reports of professional by itself, a recording instrument from the hospital and copies of the notification form of cases. The project was approved by the Ethics Research Center of Health Sciences of the Federal University of Pernambuco/UFPE with protocol number 13/10. All cases were considered of September 2006, when began using the Notification Form from the Ministry of Health until December 2008. Results: the most notification was cases against the child (n=20, 46,51%), while there isn’t registration of cases against the elderly. Professionals who often made the notification were doctors (n=22, 51.16%) and psychologists (n=12, 27,91%). The Notification Form was used in only 41,86% of cases. Conclusion: the data underscore the under-reporting. Further research should verify the cause of poor service (lack of commitment, lack of specific training, among others) so that they can perform actions to make better situation. Descriptors: violence; epidemiology; public health; mandatory reporting. RESUMO Objetivo: elucidar a situação da notificação dos casos de violência em um hospital universitário do Recife no inicio das ações de capacitação e sensibilização dos profissionais para essa questão. Método: foi realizado um estudo observacional do tipo corte transversal. A coleta de dados foi realizada a partir dos encaminhamentos realizados para o Serviço Social do Hospital das Clínicas da Universidade Federal de Pernambuco/HC/UFPE por meio de relatórios dos profissionais, instrumento de registro próprio do hospital e cópias das Fichas de Notificação dos casos. O projeto foi aprovado pelo Comitê de Ética em Pesquisa do Centro de Ciências da Saúde/UFPE com número de protocolo 13/10. Foram considerados todos os casos de setembro de 2006, quando iniciou o uso da Ficha de Notificação do Ministério da Saúde até dezembro 2008. Resultados: a maior notificação foi de casos contra à criança (n=20, 46,51%), ao passo que não consta registro de casos contra idosos. Os profissionais que mais notificaram foram os médicos (n=22, 51,16%) e os psicólogos (n=12, 27,91%). A Ficha de Notificação foi usada em apenas 41,86% dos casos. Conclusão: os dados ressaltam a sub-notificação. Pesquisas posteriores devem verificar a causa da pouca notificação (falta de compromisso, falta de formação específica, entre outras), para que se possam realizar medidas para melhorar o quadro. Descritores: violência; epidemiologia; saúde pública; notificação de abuso. RESUMEN Objetivo: conocer la situación de la notificación de casos de violencia en un hospital universitario en Recife al inicio de las acciones de formación y sensibilización del profesional de esta cuestión. Método: se realizó un estudio observacional, transversal. Recolección de datos se realiza através de consultas que el Servicio Social del Hospital de Clínicas, Universidad Federal de Pernambuco/HC/UFPE por los informes de profesionales de por sí, un instrumento de registro del hospital y copia del Formulario de Notificación de los casos. El proyecto fue aprobado por el Centro de Ética de la Investigación de las Ciencias de la Salud/UFPE com el número de protocolo 13/10. Se consideraron todos los casos de septiembre de 2006, cuando comenzó a usar el Formulario de Notificación del Ministerio de Salud hasta diciembre de 2008. Resultados: la mayoría de los casos de notificación fue contra el niño (n=20, 46,51%), mientras que no hay registro de casos en contra de los ancianos. Los profesionales que a menudo hace la notificación eran médicos (n=22, 51,16%) y los psicólogos (n=12, 27,91%). El Formulario de Notificación se utilizó en sólo 41,86% de los casos. Conclusión: los datos ponen de relieve la subnotificación. Las investigations futuras deberían verificar la causa de la notificación de baja (falta de compromiso, la falta de formación específica, entre otros) de modo que puedan llevar a cabo acciones para mejorar la situación. Descriptores: violencia; epidemiología; salud pública; notificatión obligatoria.